PERAN PEMUDA LINTAS AGAMA DALAM MENINGKATKAN KERUKUNAN UMAT BERAGAMA DI PROVINSI KALIMANTAN TIMUR - Deandlles Christover (Jurnal Paradigma (JP), 2019)
The purpose of this research is to find out how the role of the Interfaith Youth in increasing the harmony of religious people in East Kalimantan Province so as to create a harmonious pluralistic society. This research is descriptive qualitative. The data analysis used is an interactive model data analysis presented by Miles, Huberman, and Saldana, where data analysis consists of data collection, data condensation, data presentation and conclusion drawing. This study uses secondary data collection techniques by conducting library research and other secondary data sources as well as conducting research directly into the field to obtain primary data through in-depth interviews. From the results of research conducted, it shows that the Role of Youth Interfaith in Increasing Harmony in Religious Communities in East Kalimantan Province shows that so far the role of Interfaith Youth has been going well, this is because FKUB and Interfaith Youth are considered capable of supporting the conduciveness of two important elements in society , namely parents and young people. This is reinforced by the fact that religious conditions in East Kalimantan are relatively safe and peaceful.Keywords: Role, Interfaith, Youth, Harmonious